ANALISIS REAKSI PASAR MODAL INDONESIA TERHADAP PERISTIWA PENGUMUMAN PANDEMI COVID-19 PADA INDEKS SAHAM KELOMPOK INDUSTRI TERPILIH TAHUN 2020 - Athika Putri; Rokhmawati Andewi; Fitri Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to analyze the difference in abnormal returns before and after theannouncement of the COVID-19 pandemic in Indonesia on the stock index ofselected industrial groups. The population in the study was 63 companies listedon the Indonesia Stock Exchange in 2020. Data analysis was carried out with anobservation period of 11 days. The test used is a non-parametric test, namely theWilcoxon Signed Rank T Test and the Mann Whitney test. The results show thatthere is a significant difference in abnormal returns in the prospective stockgroup, there is no significant abnormal return difference in the less prospectivestock group, there is no significant abnormal return difference in the two groupsin the period before the event, there is no significant abnormal return differencebetween the two groups. two groups of post-event period. Keywords : Covid-19 Pandemic, Abnormal Return